Flight from the Satanic City: the American "Mainstream" and the Rejection of Cosmopolitanism - Matthews, Fred (Cahiers de recherche sociologique, 1990)
SummaryMainly using points taken from a survey of Californian daily newspapers Fred Matthews tries to dissect and explain the rise of contemporary "Mainstream" America. He introduces us to the way three paradigmatic historians, C. A. Beard, R. Hof stadter and P. Miller, have accounted for the sources of this current which can be seen as an escape from the perils of the open society and a refuge in a commoditized pseudo-Gemeinschaft.